2014
DOI: 10.1007/s40140-014-0058-5
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Postoperative Pain Therapy for Thoracic Surgery

Abstract: The efficient and potent treatment of pain accompanied with thoracic surgery is fundamental and beneficial for patients, since severe postoperative pulmonary complications and the incidence of chronic pain will be reduced. In this systematic review evidence-based strategies in preventing and treating pain after thoracic surgery will be discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 101 publications
1
1
0
1
Order By: Relevance
“…The results of our study are in agreement with the results of the systematic review done by Loop et al (8) who found that the use of either TEA or TPVB (thoracic paravertebral block) provides comparable and effective analgesia for thoracic surgery. TPVB reduces the incidence of post-operative pulmonary complications and post-operative hypotension.…”
Section: Resultssupporting
confidence: 92%
“…The results of our study are in agreement with the results of the systematic review done by Loop et al (8) who found that the use of either TEA or TPVB (thoracic paravertebral block) provides comparable and effective analgesia for thoracic surgery. TPVB reduces the incidence of post-operative pulmonary complications and post-operative hypotension.…”
Section: Resultssupporting
confidence: 92%
“…Pain after thoracic surgery is generally considered to be from moderate to severe and could affect pulmonary function by reducing deep breathing and coughing ability, resulting in reduced clearance of secretions, atelectasis and pneumonia;[1] nonetheless, severe postoperative pain in thoracic surgery is associated with a higher rate of pain chronicization. [2] For these reasons, optimal pain management after thoracic surgery is mandatory since without an effective pain control patients may have an adverse outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Para Heck et al (2004) o não-controle da dor no PO pode levar a alterações de prova de função respiratória. Observa-se o aparecimento de atelectasia, redução da perfusão/ventilação, hipoxemia, síndrome da dor crônica em mais de 50% dos pacientes, em Loop et al (2014) e Huang & Sakata, (2016), bem como trombose venosa profunda (Appleton, 2018) e complicações cardíacas (Van Heren et al 2018).…”
Section: Introductionunclassified